In Vivo and Ex Vivo Gene Therapy for Inherited and Non-Inherited Disorders - Bachtarzi, Houria (IntechOpen, 2019)
Ongoing advances in pharmaceutical biotechnology have paved the way to ground-breaking new biological therapeutic modalities, offering the possibility of a durable curative approach for a number of life-threatening diseases, for which the medical need is as yet unmet. Over the past decades, gene therapy has seen a massive transformation from a proof-of-concept approach to a clinical reality culminating in the regulatory approval of state-of-the-art products in the European Union and in the United States. This book captures some of the scientific progresses notably in gene transfer technologies and translational development of in vivo and ex vivo gene therapy interventions in the treatment of a broad range of complex and debilitating non-inherited and inherited disorders such as: human immunodeficiency virus 1 (HIV-1) infection, cancer, cystic fibrosis, hereditary retinopathies, haemophilia B, cardiac diseases, and chronic liver fibrosis.